Going Places : Slovenian Women's Stories on Migration - Milharčič-Hladnik, Mirjam; Mlekuž, Jernej (Book collections on Project MUSE., 2014)
Going Places is a narrative of a century of Slovenian women's immigration stories. The book traces the migration of these Central European women to several destinations including Argentina, Egypt, Italy, and the United States. The research has been carefully culled from the subjects' letters, personal diaries, and oral interviews. What results is a story that covers the span of three to four generations. The book highlights in biography the story of identity under construction. Each woman's identity surpasses ethnic, national identity or belonging, but at the same time, contains different elements of identity transformation at different stages of the narrator's life. As one narrator said, "While their [the women's] suitcases may be light with personal belongings, their stamina, strength and determination and emotional commitment would sink a battleship."--Publisher description